(untitled) (Research, Society and Development, 2024)
Objectives: To identify situations that generate tension in caregivers of elderly people cared for in the geriatrics nursing outpatient clinic and describe the relationship between situations that generate tension in caregivers and the elderly’s safety at home. Method: Exploratory and descriptive field research, qualitative. The participants were 15 caregivers of elderly people treated at the Geriatrics Nursing Outpatient Clinic of a University Hospital in Rio de Janeiro. In data collection, a semi-structured individual interview script and sociocultural identification form were used. Results: The findings made it possible to identify that the interviewees presented different levels of tension, highlighting biopsychosocial, economic and historical-cultural factors, which are the main causes of risks to patient safety at home. Conclusion: Given the difficulties highlighted by caregivers, it is necessary to seek a social support network and offer guidance in order to minimize the impacts that the tension of caring can cause.